Pengaruh Gadget terhadap Perkembangan Sosial Anak Sekolah Dasar - Putri Sofiatul Maola; Triana Lestari (EduPsyCouns: Journal of Education, Psychology and Counseling, 2021)
In the current era, technology can easily penetrate all regions and develop very fast. One of them is a gadget, gadgets are used in almost all circles, from parents to young people. Especially now that is the center of attention and conversation, namely gadgets that are widely used among elementary school children. Of course this can affect the social development of his personality. Therefore, the research was conducted using a qualitative method through a descriptive analytic approach, in which the theory or basis of discussion was taken from the results of literature studies such as books, articles and journals. As we know as the nation's future successors, of course children must be provided with positive things that can add to their horizons. Indeed, gadgets can be useful if used wisely and as well as possible, but for children, it is necessary to have strict supervision from their parents to always monitor their children while using gadgets, because from the other side, gadgets can also bring negative things. Therefore, parents as much as possible should be wise to their children in using gadgets.